The Influence of Corporate Social Responsibility Effectiveness on Community Welfare: A Study of Social Value Exchange in Rural Infrastructure Development - Raihan Adha Rahman Pohan; Maidalena Maidalena; Fitri Hayati (Celebes Scholar pg, 2025)
Corporate Social Responsibility has increasingly been positioned as a mechanism through which private enterprises engage with community welfare, particularly in contexts where public development efforts face structural limitations. This study examines the effectiveness of a Corporate Social Responsibility program in the form of road infrastructure development and its relationship with community welfare in Kampung Lalang Hamlet, North Sumatra. Using a quantitative approach, data were collected from 72 community members through structured questionnaires measuring perceived CSR effectiveness and welfare across educational, health, and economic dimensions. The data were analyzed using validity and reliability testing, classical assumption testing, and simple linear regression analysis. The results indicate a positive and statistically significant relationship between CSR program effectiveness and community welfare, with a substantial proportion of welfare variation explained by the effectiveness of the CSR intervention. These findings suggest that infrastructure-oriented CSR programs can shape community welfare through improved accessibility, service utilization, and economic activity when implemented in ways that align with local needs and social conditions.